Gerbil middle-ear sound transmission from 100 Hz to 60 kHz - Ravicz, Michael E. (Acoustical Society of America, 2008)
Middle-ear sound transmission was evaluated as the middle-ear transfer admittance H(MY) (the ratio of stapes velocity to ear-canal sound pressure near the umbo) in gerbils during closed-field sound stimulation at frequencies from 0.1 to 60 kHz, a range that spans the gerbil’s audiometric range. Similar measurements were performed in two laboratories. The H(MY) magnitude (a) increased with frequency below 1 kHz, (b) remained approximately constant with frequency from 5 to 35 kHz, and (c) decreased substantially from 35 to 50 kHz. The H(MY) phase increased linearly with frequency from 5 to 35 kHz, consistent with a 20–29 μs delay, and flattened at higher frequencies. Measurements from different directions showed that stapes motion is predominantly pistonlike except in a narrow frequency band around 10 kHz. Cochlear input impedance was estimated from H(MY) and previously-measured cochlear sound pressure. Results do not support the idea that the middle ear is a lossless matched transmission line. Results support the ideas that (1) middle-ear transmission is consistent with a mechanical transmission line or multiresonant network between 5 and 35 kHz and decreases at higher frequencies, (2) stapes motion is pistonlike over most of the gerbil auditory range, and (3) middle-ear transmission properties are a determinant of the audiogram.